2023
DOI: 10.1002/adsc.202201404
|View full text |Cite
|
Sign up to set email alerts
|

COAP‐Palladium‐Catalyzed Asymmetric Linear Allylic Alkylation of Vinyl Benzoxazinanones for Multifunctional 3,3′‐Disubstituted Oxindole Derivatives

Abstract: A Pd‐catalyzed enantioselective linear‐allylic alkylation of vinyl benzoxazinanones with a series of 3‐substituted oxindoles was reported in the presence of a chiral oxamide‐phosphine ligand (COAP−Bn) under mild reaction conditions. A series of optically active multifunctional 3,3′‐disubstituted oxindole derivatives bearing a quaternary stereogenic center and a linear aryl amino side chain were respectively obtained in 55–98% yields with 96–99% ee for 3‐(hetero)aryl substituted oxindoles. The developed protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…More recently, Wang et al illustrated an enantioselective linear‐allylic alkylation of vinyl benzoxazinones 1 with 3‐substituted oxindoles 72 via the complex of palladium with chiral oxamide‐phosphine ligand 30 developed by their group, allowing a facile access to series of optically active multifunctional 3,3’‐disubstituted oxindole derivatives 73 bearing a quaternary stereogenic center and a linear aryl amino side chain in 55–98% yields with 96–99% ee (Scheme 25). [42] Notably, the developed protocol demonstrated that the oxamide‐phosphine ligands could serve as a privileged chiral ligand to construct diverse chiral 3,3‐disubstituted oxindole compounds with various quaternary stereogenic centers, such as aza ‐, thio ‐ or all‐carbon quaternary stereogenic centers.…”
Section: Catalytic Asymmetric Reactions Of Vinyl Benzoxazinonesmentioning
confidence: 99%
“…More recently, Wang et al illustrated an enantioselective linear‐allylic alkylation of vinyl benzoxazinones 1 with 3‐substituted oxindoles 72 via the complex of palladium with chiral oxamide‐phosphine ligand 30 developed by their group, allowing a facile access to series of optically active multifunctional 3,3’‐disubstituted oxindole derivatives 73 bearing a quaternary stereogenic center and a linear aryl amino side chain in 55–98% yields with 96–99% ee (Scheme 25). [42] Notably, the developed protocol demonstrated that the oxamide‐phosphine ligands could serve as a privileged chiral ligand to construct diverse chiral 3,3‐disubstituted oxindole compounds with various quaternary stereogenic centers, such as aza ‐, thio ‐ or all‐carbon quaternary stereogenic centers.…”
Section: Catalytic Asymmetric Reactions Of Vinyl Benzoxazinonesmentioning
confidence: 99%